Association of Maternal Weight Gain and Fetal Weight at Term Pregnancy: A Cross Sectional Study (Journal of Chittagong Medical College Teachers' Association, 2014)
To evaluate the relationship between maternal weight gain and fetal weight in term pregnancy. An observational study was carried out in a private clinic in Cox's Bazar, from March 2011 to March 2012. Total 200 mothers with singleton pregnancy were selected. Maternal weights were recorded in 1st trimester and 3rd trimester. Fetal weights were noted at 37 completed weeks of gestation by ultrasonography. Most (63%) of the women were 20 - 29 years of age (mean 24.1±5.3) and 70.5% women got married at the age of 16 — 20 years (mean 18.71±2.79) and 11% of them had 3 children had